Polimorfisme Protein Darah Itik Pegagan dengan Metode PAGE - Meisji Liana Sari; Ronny Rachman Noor; Peni S. Hardjosworo; Chairun Nisa (Jurnal Agripet, 2011)
polymorphism of blood protein pegagan duck by PAGE methodABSTRACT. Pegagan duck is one of local duck species which comes from Ogan Ilir (OI) Regency, South Sumatera. This species is not popular, yet. But, it has spread out along Ogan river which comprises of three districts e.g Tanjung Raja, Inderalaya and Pemulutan. The ecosystem in this three districts is dominated by swampy area. As far, there is relatively limited information of Pegagan duck compared to another local duck. So, for the first step was done a reseach to identify genetic characteristic from blood protein analyses by electrophoresis method. It is expected that this information will become the bases in determining of the policy of Pegagan duck development. Polymorphism analyses of blood protein was done with 9 duck samples which taken randomly from 400 pegagan ducks. Protein locus observed were albumin (Alb), post albumin (Pa), transferrine (Tf), post transferrine-1 (Ptf-1), and post transferrine-2 (Ptf-2). Polymorphism analyses of blood protein of pegagan duck was characterized by allele A in locus Transferrine (TfA), Post transferrine-1 (Ptf-1A) and Post transferrine-2 (Ptf-2A) . Genetic diversity based on blood protein of Pegagan duck showed that gen frequency value in a range of 0,11 0,94 and high heterozygosis value that was 0,62 %.